ANALISIS PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH APARATUR SIPIL NEGARA - Zainab Ompu Jainah; Intan Nurina Seftiniara; Muhammad Arief Rahman (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2021)
The crime of corruption is the misappropriation or misuse of state money for personal or group interests. The problem that most often occurs among the community, this Crime of Corruption is widely carried out by the State Civil Apparatus as a person who has a position or has a certain position that is wrongly used, basically this kind of deviant behavior that is very worrying can cause problems among the community, this Corruption Crime also has a very negative impact on the financial losses of the state,   Criminal offenders must be held accountable for their actions in the form of imprisonment, fines or dismissal with disrespect as a state civil apparatus which of course in committing the crime is known there are several factors that result in the perpetrator committing a criminal act of corruption, due to criminal acts committed by the perpetrator resulting in an impact on the community, which resulted in state financial losses due to the misuse of state money in the form of  corruption by the perpetrators. The crime of corruption is the misappropriation or misuse of state money for personal or group interests. The problem that most often occurs among the community, this Crime of Corruption is widely carried out by people who have a position or have a certain position basically deviant behavior like this which is very worrying can cause problems among the community, this Crime of Corruption also has a very negative impact on the financial losses of the country